Development of forward osmosis membranes modified by cross-linked layer by layer assembly for brackish water desalination - Nidal Hilal (Journal of Membrane Science, 2019)
Forward osmosis membranes having high water flux and minimum reverse solute flux are the ideal membranes for forward osmosis process. In this work, we report the use of a LbL surface modification strategy to fabricate a novel positively charged FO membranes. The main purpose of this work was to synthesize an effective selective layer onto a commercial PES ultrafiltration membrane, which functioned as a support layer, to provide the best performance for treatment of brackish water. The new membranes containing a mixing ratio of 0.1 MPDADMAC: 0.001 MCMCNa in the polyelectrolyte complex exhibited the best performance in terms of minimum reverse solute flux and acceptable water flux as compared to that for membranes containing a mixing ratio of 0.1 MPDADMAC: 0.01 MCMCNa. This improved performance and physicochemical properties of the new membranes were explored by various analytical techniques and were compared to the pristine membrane. Firstly, Structural characterization revealed that the new selective layer was homogenous, uniform and strongly adhered to the substrate resulting in excellent water permeability and acceptable reverse solute flux. Secondly, it was found that the optimal curing temperature was 60 OC for 4 hours that contributed to enhanced membrane performance. Lastly, the developed ranking protocol was adopted to optimize the membrane performance in terms of the water permeability coefficient (A) and solute permeability coefficient (B). According to this optimization procedure, the best performing membrane was membrane coated 2.5 bilayers which had water permeability and solute permeability coefficients of 23.1 L m−2 h−1 bar-1 and 1.54 L m−2 h−1 respectively.